Rancang Bangun Sistem Monitoring Kebocoran ydrofluorocarbon (HFC) pada Cold Storage System Berbasis IoT di Kapal AHTS - Arjun Widiansyah; Sonhaji Sonhaji; Shofa Dai Robbi (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
This research aims to design and developing a hydrofluorocarbon (HFC) leak monitoring system in the cold storage cooling system on the Anchor Handling Tug Supply (AHTS) ship by utilizing Internet of Things (IoT) technology. HFC leaks in cooling systems can cause environmental hazards and operational inefficiencies. The proposed system integrates sensors and IoT devices to continuously monitor HFC levels, detect leaks in real-time, and provide instant alerts to crew and management. The system architecture includes sensors for HFC detection, a microcontroller for data processing, and a communication module for data transmission to a central monitoring platform. Real-time data can be accessed through a user-friendly interface, enabling timely intervention and maintenance. Initial testing shows that the system is effective in identifying and reporting HFC leaks, potentially reducing environmental impacts and improving the safety and efficiency of cold storage operations on AHTS vessels. Further development and extensive field testing are planned to refine the system and validate its performance across a wide range of operational conditions.